2006
DOI: 10.1002/ajh.20669
|View full text |Cite
|
Sign up to set email alerts
|

New‐onset and idiopathic thrombotic thrombocytopenic purpura: Incidence, diagnostic validity, and potential risk factors

Abstract: Objective: The aim of this study was to determine the incidence rate for new-onset and idiopathic thrombotic thrombocytopenic purpura (TTP) among adults 20-64 years old, the validity of diagnostic criteria, and potential risk factors for TTP.Methods: This retrospective observational study analyzed automated administrative data from 11 geographically dispersed U.S. health plans. Cases of TTP were identified based on the presence of an inpatient hospital claim for TTP (ICD-9-CM 446.6) between 1/1/97 and 12/ 31/0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Thienopyridine-associated TTP rates were derived from one survey of directors of six therapeutic plasma exchange centers reported by our group and a second survey of nine interventional cardiology centers reported by Steinhubl et al, 9,14 phase III clinical trial reports, [15][16][17][18][19][20][21][22] and analyses of insurance claim files and group practice databases. 23,24 As reported in our 2007 and 2009 reviews, 8,13 plasma samples obtained from patients with thienopyridine-associated TTP included in the Surveillance Epidemiology and Risk Factor for TTP (SERF-TTP) project were evaluated for ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) activity, as measured with standard assays. 25 The inhibitory activity of the autoantibodies was determined by mixing TTP plasma samples at various dilutions with normal plasma and measuring proteinase activity of the mixture, as previously reported and described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thienopyridine-associated TTP rates were derived from one survey of directors of six therapeutic plasma exchange centers reported by our group and a second survey of nine interventional cardiology centers reported by Steinhubl et al, 9,14 phase III clinical trial reports, [15][16][17][18][19][20][21][22] and analyses of insurance claim files and group practice databases. 23,24 As reported in our 2007 and 2009 reviews, 8,13 plasma samples obtained from patients with thienopyridine-associated TTP included in the Surveillance Epidemiology and Risk Factor for TTP (SERF-TTP) project were evaluated for ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) activity, as measured with standard assays. 25 The inhibitory activity of the autoantibodies was determined by mixing TTP plasma samples at various dilutions with normal plasma and measuring proteinase activity of the mixture, as previously reported and described.…”
Section: Methodsmentioning
confidence: 99%
“…The second study, reported by FDA safety personnel, did not identify any cases of ticlopidine-or clopidogrel-associated TTP among 16.4 million person-years of observation among 11 private health care plans (2001 to 2004 data). 24 During these study years, clopidogrel use had increased dramatically whereas ticlopidine use declined. Incidence of TTP among patients with coronary artery stent placement is about 1 in 1,500 with ticlopidine.…”
Section: Administrative Databases-estimating Incidence Rates Of Ticlomentioning
confidence: 99%
“…The incidence rate of TTP was estimated to be 1.45-3.8 per 10 6 person-years in 4 previous studies [6][7][8][9]. In only one study were the TTP cases defined with ADAMTS13 analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Diversi studi hanno cercato di stimare l'incidenza annua di PTT [1][2][3]. Nel Registro dell'Oklahoma, in cui la diagnosi di PTT è stata confermata dal dosaggio di ADAMTS13, l'incidenza è di 1,74 casi per milione anno-persona.…”
Section: Introduzione Caso Clinicounclassified